62.7k views
2 votes
1. 2(a + 6) - 12 - a = 19 Simplify then Solve

2. -(2a + 3) + 3 + 9a = 14 Simplify then
Solve

3. -3(a - 5) + 7a - 15 = 16 S then S

4. 5(a - 1) + 8a + 5 = 78 STS

5. 3a + 2(a - 6) + 12 = 15

User CoPLaS
by
5.3k points

1 Answer

2 votes

Answer:

Let's solve your equation step-by-step.

2(a+6)−12−a=19

Step 1: Simplify both sides of the equation.

2(a+6)−12−a=19

(2)(a)+(2)(6)+−12+−a=19(Distribute)

2a+12+−12+−a=19

(2a+−a)+(12+−12)=19(Combine Like Terms)

a=19

a=19

Answer:

a=19

Explanation:

User Tejas HS
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.